Critical limit of diameter-to-thickness ratio for inner tubes of DSSTCC columns. (15th July 2022) - Lin, Chenghuan; Zhou, Jikai; Chen, Yijie
Highlights: A simplified buckling analysis model for inner steel tubes is proposed. A recommended critical limit of diameter-to-thickness ratio ( D / h ) is given. An empirical formula is fitted to estimate the critical limit of ( D / h ) ratio. Setting stiffeners for inner tubes can relax the restriction on the ( D / h ) ratio. The proposed method can work well when inner tubes take other constitutive models. Abstract: To improve the confinement efficiency of steel tubes to the sandwiched concrete, the concept of double skin steel tubes confined concrete (DSSTCC) columns was proposed. This paper aims to theoretically investigate the local stability of inner steel tubes in DSSTCC columns. Firstly, considering that the stress state and failure mode of the inner steel tube are similar to those of the fixed circular arch subjected to a uniform radial load, the arc section of the inner steel tube was simplified into a circular arch for stress analysis. Secondly, the expected value of the in-plane elastic ultimate axial compressive stress of the circular arch was solved by the Monte Carlo method, and the ratio of its value to the yield stress was used to characterize the stable state of the inner tube. Then, the influence of the maximum included angle corresponding to the formed circular arch on the result was discussed, and an empirical formula was given to obtain a reasonable estimation of the critical limit of diameter-to-thickness ratio. Finally, it can be seen from the analysis that the method proposed in this paper is suitable for inner tubes made of the material with an elastic perfectly-plastic model, a bilinear model, or a bilinear plus nonlinear hardening model. These results are a contribution to the buckling analysis of inner tubes.